Conference Scene: Report on the 8th Annual Cold Spring Harbor/Wellcome Trust meeting on Pharmacogenomics and Personalized Medicine. (March 2011) - Carr, Daniel F; Alfirevic, Ana
The joint Cold Spring Harbor/Wellcome Trust Conference on pharmacogenomics, held in the USA and the UK in alternate years, focuses on the growing contribution of genomic technologies to the study of variable human responses to therapeutic agents. The meeting brings together researchers from academic, medical, regulatory and industrial sectors who discuss the current issues for the clinical implementation of pharmacogenomics, and to offer a look into the future advancements of technologies and the biostatistic and bioinformatic methodologies used to analyze arising complexity.